2011
DOI: 10.1088/0004-637x/730/2/74
|View full text |Cite
|
Sign up to set email alerts
|

Power of Observational Hubble Parameter Data: A Figure of Merit Exploration

Abstract: We use simulated Hubble parameter data in the redshift range 0 ≤ z ≤ 2 to explore the role and power of observational H(z) data in constraining cosmological parameters of the ΛCDM model. The error model of the simulated data is empirically constructed from available measurements and scales linearly as z increases. By comparing the median figures of merit calculated from simulated datasets with that of current type Ia supernova data, we find that as many as 64 further independent measurements of H(z) are needed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
123
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(129 citation statements)
references
References 72 publications
6
123
0
Order By: Relevance
“…[32] and [33]. We found that with current quality of simulated data, the GP method can recover and distinguish models with a different cosmic curvature with an order of 10 Based on a one-parameter extension to the sixparameter ΛCDM model, CMB data [9,34,35] provide a strong constraint on Ω (0)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[32] and [33]. We found that with current quality of simulated data, the GP method can recover and distinguish models with a different cosmic curvature with an order of 10 Based on a one-parameter extension to the sixparameter ΛCDM model, CMB data [9,34,35] provide a strong constraint on Ω (0)…”
Section: Discussionmentioning
confidence: 99%
“…Adopting the methodology in [32], we draw the error from a Gaussian distribution: σ E ∼ N (σ, ǫ) withσ = (σ + + σ − )/2 and ǫ = (σ + − σ − )/4, where σ + and σ − are the two straight lines that bound the uncertainties σ(z) of the observational E(z) data from above and below, respectively. Then E(z) sim is sampled from the Gaussian distribution E(z) sim ∼ N (E(z) f id , σ E ), where E(z) f id is the theoretical value from the fiducial model.…”
Section: Mock Datamentioning
confidence: 99%
“…The H(z) data at 11 different redshifts were determined from the differential ages of red-envelope galaxies (Stern et al 2010), and two more Hubble parameter data points H(z = 0.24) = 79.69 ± 4.61 and H(z = 0.43) = 86.45 ± 5.96 were obtained by Gaztañaga et al (2009) from observations of BAO peaks (for a review of the observational H(z) data, see Zhang et al 2010). Studies using these newly H(z) data for cosmological constraint include Gong et al (2010), Liang et al (2010a), , Cao & Liang (2010), Zhang (2011), andWang (2010c). We emphasize the use of the Hubble constant H 0 in our analysis.…”
Section: The Observational H(z) Datamentioning
confidence: 99%
“…In Ref. [37] the power of OHD in the context of ΛCDM model has been assessed. With the increase of high quantity OHD, the power of OHD constraining void model should also be greatly improved for constraining the void models [10].…”
Section: Discussionmentioning
confidence: 99%